How to Do Things with Emojis: The Pragmatic Functions of Emojis in Teacher-Student Interaction through Wechat (Sinología hispánica. China Studies Review, 2020)
As efficient tools in online interaction, Emojis have attracted ample attention fromresearchers in diverse fields, stressing that its pragmatic values deserve further systemic exploration.Against this background, this paper investigates the pragmatic functions of emojis through retrievinginteractive data between teachers and students in Wechat rooms. A total of 5 volunteers (4 teachersand 1 student) were invited to collect data from their teacher-student Wechat groups respectively.Forty-eight types of emoji in the corpus were described and analyzed, finally classified into 3 pragmaticfunctions: illocutionary function, interpersonal function and textual function. Specifically, emojis can:i) work as indicators of literal force (secondary illocutionary act) or indirect force (primary illocutionaryact). ii) work as rapport management strategies to maintain or enhance the relationship between/amonginterlocutors. iii) work as structural constituents, which will contribute to the opening, continuing orclosing of a conversation. Accordingly, these findings would contribute to the enrichment of theoreticalstudies of emojis, and the understanding of online discourse in mediated forms.